Epipremnum aureum (Araceae) roots associated simultaneously with Glomeromycotina, Mucoromycotina and Ascomycota fungi - Muthukumar, Thangavelu; Karthik, Shanmugam (Botanica Complutensis, 2021)
Only a small number of aroids are examined for their symbiosis with glomeromycotean arbuscular mycorrhizal (GAM) fungi and the ascomycetous dark septate endophytic (DSE) fungi. Therefore we examined the aerial and terrestrial adventitious roots of Epipremnum aureum for the endophytic association and the soils for GAM spores. The aerial roots of E. aureum were free from fungal structures, whereas the terrestrial roots were colonized by GAM, fine root endophyte (FRE), and DSE fungi. The major portion of the terrestrial roots was colonized by FRE fungi followed by GAM and DSE fungi. The colonization pattern was a complex of Arum-Paris and intermediate types. Spores of Acaulospora, Funneliformis, Rhizophagus, Rhizophagus and Sclerocystis were isolated from the root zone soils. The results show that E. aureum can establish symbiosis with a wide range of endophytic fungi and FRE symbiosis is reported for the first time in aroids.